A rapid review of the impact of COVID‐19 on clinical supervision practices of healthcare workers and students in healthcare settings. (16th July 2022) - Martin, Priya; Tian, Esther; Kumar, Saravana; Lizarondo, Lucylynn
Abstract: Aims: To synthesize available data on the impact of the COVID‐19 pandemic on clinical supervision practices of healthcare workers and students in healthcare settings. Design: A quantitative rapid review of the literature. Data Sources: A search of MEDLINE, Embase, PsycINFO, the Cochrane Library and Scopus for English language papers published between December 2019 (initial onset of the pandemic) to March 2021. Review methods: Using the World Health Organization and Cochrane guidelines for rapid reviews, following an identification of relevant papers and data extraction, a narrative synthesis approach was used to develop themes. Results: Eight studies met the inclusion criteria. Four themes identified from data synthesis were nature and extent of disruptions to clinical supervision, unmet need for psychological support, supervisors also need support and unpacking telesupervision. Findings highlight the extent and nature of disruption to clinical supervision at the point of care. Further information on factors that facilitate high‐quality telesupervision have come to light. Conclusion: The COVID‐19 pandemic has placed tremendous burden on healthcare workers compromising their own health and well‐being. It is essential to restore effective clinical supervision practices at the point of care, so as to enhance patient, healthcare worker and organizational outcomes into the post‐COVID‐19 pandemic period. Impact: This review has provided initial evidence on the adverse impacts of the COVID‐19 pandemic on clinical supervision of healthcare workers and students at the point of care. Available evidence indicates the urgent need to restore effective and high‐quality clinical supervision practices in health settings. The review has highlighted a paucity of studies in this area, calling for further high‐quality studies.